Genetic control of cell size. - Stocker, H.; Hafen, E. (Current Opinion in Genetics and Development, 2000)
Over the past 25 years, the genetic control of cell size has mainly been addressed in yeast, a single-celled organism. Recent insights from Drosophila have shed light on the signalling pathways responsible for adjusting and maintaining cell size in metazoans. Evidence is emerging for a signalling cascade conserved in evolution that links external nutrient sources to cell size.